Impacts of Aerobic Exercise on Depression-Like Behaviors in Chronic Unpredictable Mild Stress Mice and Related Factors in the AMPK/PGC-1α Pathway - Luo, Jia; Tang, Changfa; Chen, Xiaobin; Ren, Zhanbing; Qu, Honglin; Chen, Rong; Tong, Zhen (International journal of environmental research and public health, 2020)
This study was to study the impact of aerobic exercises on the chronic unpredictable mild stress (CUMS) in mice, and to discuss the possible mechanism from the skeletal muscle AMPK/PGC-1α energy metabolism signaling pathway. The healthy male mice were randomly divided into Control Group (CG), Model Group (MG), and Model Exercise Group (ME).Twelve stress methods were adopted for four weeks (28 days) to establish the depression model. ME was subject to aerobic training plan after the model was established. The weight of the mice was recorded weekly. After the experimental intervention, the three groups of mice were subjected to behavioral assessment tests. Western blotting, RT-PCR, and ELISA were performed to test AMPK, p-AMPK, PGC-1α, and ATP in skeletal muscle. There were no significant difference in body weight between the three groups. CUMS leaded to significant decline in behavioral scores. and the p-AMPK and PGC-1α decreased significantly. But boosted ATP content. Aerobic exercise enhanced the expressions of p-AMPK and PGC-1α, increased the ratio of p-AMPK/AMPK, boosted ATP content. And improved behavioral scores significantly. Chronic stress-induced depression-like behavior was improved significantly by Aerobic exercise. The mechanism of aerobic exercise for improving depressive symptoms in mice with chronic stress depression may be related to influence AMPK/PGC-1α pathway.